The Relationship Of Efficacy With Burnout Nursing Implementation In Sajiwani Gianyar Hospital - Ni Putu Wiwin Purniyawati; Ni Made Nopita Wati; Niken Ayu Merna Eka Sari (Jurnal MIDPRO, 2021)
Unresolved work stress can lead to emotional fatigue, a decline of personal achievement hereinafter called Burnout. The impact of burnout is decreased performance. The way individuals or nurses can do to mitigate the impact of burnout is with Self Efficacy. High self-efficacy levels will believe that they are able to do something to change the barriers around it while someone with low self-efficacy considers himself incapable of working on everything that is around him. This research aims to know the self-efficacy relationship with an implementing nurse burnout in the inpatient room in RSUD Sanjiwani Gianyar year 2020. This research is quantitative with non probability sampling research design with cross sectional approach. The technique used in sampling is the total sampling technique with the number of samples as much as 60 respondents. The instruments used in this study are questionnaires. Data analysis is carried out using the Rank Spearman test. The results obtained by most nurses have a high self efficacy that is as much as 29 people (48.3%) and burnout as much as 51 people (85.0%). The P-value result of 0.000 (P < 0.05) with a direction of negative correlation is the higher the level of self efficacy nurse then the lower the level of burnout nurses in RSUD Sanjiwani Gianyar. Belief is one’s ability to use knowledge and skills effectively can reduce burnout. Further research is expected to conduct research with a greater population level in order to be representative and can be generalized